Review: Diversity, structure, and community composition of Bornean heath forest with a focus on Brunei Darussalam - IRSALINA M. IKBAL; HAZIMAH H.M. DIN; Wardah H. Tuah; Salwana Md Jaafar; NORHAYATI AHMAD; Rahayu Sukmaria Sukri (Society for Indonesian Biodiversity, 2023)
Abstract. Ikbal IM, Din HHM, Tuah WH, Jaafar SM, Ahmad N, Sukri RS. 2023. Review: Diversity, structure, and community composition of Bornean heath forest with a focus on Brunei Darussalam. Biodiversitas 24: 2814-2829. Tropical heath forests, a unique lowland forest ecosystem with high conservation value, are increasingly threatened by disturbances. Heath forests are characterized by trees of short stature and the presence of highly acidic, sandy soils with poor nutrient content. Bornean heath forests are widely studied for their diversity, structure, and community composition and are known to support endemics of high conservation value. Environmental factors and soil properties, such as topography, water availability, and nutrient status, are known to influence tree species diversity and forest structure of Bornean forests. However, factors influencing their community composition, including the role of seedling communities in influencing heath forest communities, are still not well understood. In particular, studies of tree diversity and community composition of heath forests in Brunei Darussalam have revealed high endemism and the presence of species with high conservation value. Anthropogenic threats to Bornean heath forests highlight the urgent need for an increased understanding of these forests and prioritization of their conservation. Increased insights into the ecological preferences of heath forest species are crucial for the successful restoration of degraded heath forests. The intact forest ecosystems of Brunei could provide opportunities for further ecological research on the plant communities found in these unique forests.